The role of university education in leadership preparation in Nigeria (2009)
polytechnic education system. The study was carried out ex-past facto. Subjects used in the study were purposively selected from university and polytechnic graduate employees in Ibadan and Lagos, as well as 100 purposivly selected employers who reated the two set of graduate employees produced by tertiary institutions. Two instruments which were constructed and validated by the researchers were employed in data collection. The chi-square, t-test and percentages were used to analyze the resulting dataT. Findings include, among others, that the Nigerian university system has been largely responsible for preparing leaders for the Nigeiran nation and that it does better than its polytechnic counterpart in this regard. However, it was also discovered that it lacks adequate funds and facilities to enable it discharge this fucntion adequately and credibly. It was also found that mentoring for leadership was negligible, though it is the practical component that can adequately bridge the gap between the town and the gown. Recommendations include incresed level of funding, provision of relevant facilities, mentoring and leadership as well as curricula revision to make leadership preparation a good combination of theory and practice.